Human cytomegalovirus replication cycle is regulated by hepatocyte growth factor/c-met pathway - Walid Basha (My University, 2010)
These results suggest several possible options for inhibiting HCMV replication. This work
could lead to development of therapeutic candidates for treatment of GVHD.

These results suggest several possible options for inhibiting HCMV replication. This work
could lead to development of therapeutic candidates for treatment of GVHD.
Human cytomegalovirus replication cycle is regulated by hepatocyte growth factor/c-met pathway